AYURAKSHA, a prophylactic Ayurvedic immunity boosting kit reducing positivity percentage of IgG COVID-19 among frontline Indian Delhi police personnel: A non-randomized controlled intervention trial - Nesari, Tanuja; Kadam, Sujata; Vyas, Mahesh; Huddar, Vitthal G.; Prajapati, Pradeep Kumar; Rajagopala, Manjusha; More, Anand; Rajagopala, Shri krishna; Bhatted, Santosh Kumar; Yadav, Rama Kant; Mahanta, Vyasdeva; Mandal, Sisir Kumar; et al. (Frontiers in Public Health, 2022)
Objective The world continues to face the COVID-19 crisis, and efforts are underway to integrate traditional medicine interventions for its effective management. The study aimed to determine the efficacy of the “AYURAKSHA” kit in terms of post-interventional percentage of COVID-19 IgG positivity, immunity levels, and quality of life (QoL) against COVID-19. Method This was a non-randomized controlled, prospective intervention trial, done after the distribution of 80,000 AYURAKSHA kits (constituent of Sanshamani Vati, AYUSH Kadha, and Anu Taila) among Delhi police participants in India. Among 47,827 participants, the trial group (n = 101) was evaluated with the positivity percentage of IgG COVID-19 and Immune Status Questionnaire (ISQ) scores as a primary outcome and the WHO Quality of Life Brief Version (QOL BREF) scores along with hematological parameters as a secondary outcome in comparison to the control group (n = 71). Results The data showed that the percentage of COVID-19 IgG positivity was significantly lower in the trial group (17.5 %) as compared to the control group (39.4 %, p = 0.003), indicating the lower risk (55.6%) of COVID-19 infection in the trial group. The decreased incidence (5.05%) and reduced mortality percentage (0.44%) of COVID-19 among Delhi police officers during peak times of the pandemic also corroborate our findings. The ISQ score and WHO-QOL BREF tool analysis showed the improved scores in the trial group when compared with the controls. Furthermore, no dysregulated blood profile and no increase in inflammation markers like C-reactive protein, erythrocyte sedimentation rate, Interleukin-6 (IL-6) were observed in the trial group. However, significantly enhanced (p = 0.027) IL-6 levels and random blood sugar levels were found in the control group (p = 0.032), compared to a trial group (p = 0.165) post-intervention. Importantly, the control group showed more significant (p = 0.0001) decline in lymphocyte subsets CD3+ (% change = 21.04), CD4+ (% change = 20.34) and CD8+ (% change = 21.54) levels than in trial group, confirming more severity of COVID-19 infection in the control group. Conclusion The AYURAKSHA kit is associated with reduced COVID-19 positivity and with a better quality of life among the trial group. Hence, the study encourages in-depth research and future integration of traditional medicines for the prevention of the COVID-19 pandemic. Clinical trial registration http://ctri.nic.in/, identifier: CTRI/2020/05/025171.